Stereotactic Body Radiotherapy for Lymph Node Oligometastases: Real-World Evidence From 90 Consecutive Patients - Burkon, Petr; Selingerova, Iveta; Slavik, Marek; Pospisil, Petr; Bobek, Lukas; Kominek, Libor; Osmera, Pavel; Prochazka, Tomas; Vrzal, Miroslav; Kazda, Tomas; Slampa, Pavel (Frontiers in Oncology, 2021)
Aims: To evaluate the efficacy and toxicity of extracranial stereotactic body radiotherapy (SBRT) in the treatment of oligometastatic lymph node involvement in the mediastinum, retroperitoneum, or pelvis, in a consecutive group of patients from real clinical practice outside clinical trials. Methods: A retrospective analysis of 90 patients with a maximum of 4 oligometastases and various primary tumors (the most common being colorectal cancers). The endpoints were local control of treated metastases (LC), freedom from widespread dissemination (FFWD), progression-free survival (PFS), overall survival (OS), and freedom from systemic treatment (FFST). Acute and delayed toxicities were also evaluated. Results: The median follow-up after SBRT was 34.9 months. The LC rate at three and five years was 68.4% and 56.3%, respectively. The observed median FFWD was 14.6 months, with a five-year FFWD rate of 33.7%. The median PFS was 9.4 months; the three-year PFS rate was 19.8%. The median FFST was 14.0 months; the five-year FFST rate was 23.5%. The OS rate at three and five years was 61.8% and 39.3%, respectively. Median OS was 53.1 months. The initial dissemination significantly shortened the time to relapse, death, or activation of systemic treatment – LC (HR 4.8, p<0.001), FFWD (HR 2.8, p=0.001), PFS (HR 2.1, p=0.011), FFST (HR 2.4, p=0.005), OS (HR 2.2, p=0.034). Patients classified as having radioresistant tumors noticed significantly higher risk in terms of LC (HR 13.8, p=0.010), FFWD (HR 3.1, p=0.006), PFS (HR 3.5, p<0.001), FFST (HR 3.2, p=0.003). The multivariable analysis detected statistically significantly worse survival outcomes for initially disseminated patients as well as separately in groups divided according to radiosensitivity. No grade III or IV toxicity was reported. Conclusion: Our study shows that targeted SBRT is a very effective and low toxic treatment for oligometastatic lymph node involvement. It can delay the indication of cytotoxic chemotherapy and thus improve and maintain patient quality of life. The aim of further studies should focus on identifying patients who benefit most from SBRT, as well as the correct timing and dosage of SBRT in treatment strategy.